Knowledge – Memory – Identity and Several More General Considerations - Havelka , Miloš (Dějiny – teorie – kritika, 2007)
Against the background of a recent discussion on the creation of an institute of ‘national memory’, this text analyses the broader issue of ‘memory’ and the politics of memory from sociological standpoints. It starts off with a general analysis of the relationships between memory, sources and historical knowledge, calls attention to the anthropological and cultural bases of the construction of memory and its ‘colonising’ and ‘isolating’ functions. It notes that deficits in the contents of individual memory and their contrafactual potential make it possible not only to legitimise political interests in various ways, but to view and evaluate analytical historical research in different ways as well. Under the heading ‘The Utraquism of Memory’, he then refers to the mutual conditionality of historical memory and ‘social forgetting’. The author elucidates the sociocultural foundations of their mutuality by means of concepts used in Jeffrey C. Alexander’s sociology of cultural traumas. In this connection, he then shows the relevance of memory both for the creation of a historical consciousness and the construction of a collective identity as well as a concrete form of solidarity.